PEDICLED ABDOMINAL FLAP FOR MALIGNANT DEFECT RECONSTRUCTION: A VIABLE ALTERNATIVE TO FREE FLAP - Kawilarang, Bertha; Utami, Putu Trisna (Universitas Airlangga, 2025)
Highlights: Pedicled abdominal flap remains a reliable reconstructive option in the era of microsurgery. Although a two-stage procedure, it provides safe and functional reconstruction. Compared to free flaps, it offers a simpler approach with fewer complications—crucial for cancer patients with limited prognosis. Abstract: Introduction: The pedicled abdominal flap, a commonly used reconstructive option, remains relevant in the era of advanced microsurgery despite the rising preference for free flaps. While free flaps offer advantages, they also carry risks of flap failure and require complex microvascular anastomosis, making them less suitable for certain patients. Case Illustration: A 48-year-old female presented with a history of a non-healing ulcer over the left upper arm due to burn scarring from a flame injury sustained 20 years prior. Following tumor resection, debridement of the defect was done which showed complete loss of skin, subcutaneous tissue, and fascia of the upper arm. A rectangle shaped skin flap was designed on the left abdominal region on the same side as the defect on the affected upper arm. A pedicled axial fasciocutaneous flap was harvested from the left lumbar area of the abdomen, utilizing the paraumbilical perforators for vascularity. Discussion: This case report highlights the use of the pedicled abdominal flap in the reconstruction of defects resulting from malignancy, emphasizing its reliability and suitability in such complex scenarios. For individuals with malignancy, the pedicled abdominal flap is often favored due to its safer, single-stage procedure, minimizing complications and re-operation risks. Conclusion: Compared to free flaps, the pedicled abdominal flap is a preferable choice in reconstructing defects in cancer patients due to its reliability, reduced risk of flap failure, and relatively simple surgical procedure. This is particularly important for cancer patients, where the focus is on achieving functional reconstruction while considering patient's prognosis.